PROFESSIONAL EXAMINATIONS. - Chamberlain, Henry T. (The Accounting Review, 1947)
Abstract The following accounting problems were prepared by the Board of Examiners of the American Institute of Accountants and were presented as the second half of the Certified Public Accountant examination in accounting practice on May 15, 1947. The candidates were allowed four and a half hours to solve problem 1 and either problem 2 or problem 3. Problem 1 was given a weight of 30 points and 20 points was assigned to either problem 2 or problem 3 From the following information, prepare a balance-sheet as at December 31, 1944, in accordance with the authorization of board of directors referred to below. The adjustments should be clearly keyed by letters or numbers on working trial balance. The Construction Corp. is engaged in a variety of construction work under contracts, the collections on which are made on the basis of engineering and architects' estimates as to stage of completion. Customers usually retain a percentage of the amount of each estimate pending completion of the contract. Gross profit on contracts has been shown in the books and financial statements in the year of completion.